Impacts of ferrate oxidation on natural organic matter and disinfection byproduct precursors. (1st June 2016) - Jiang, Yanjun; Goodwill, Joseph E.; Tobiason, John E.; Reckhow, David A.
Abstract: This study investigated the effectiveness of ferrate (Fe(VI)) oxidation in combination with ferric chloride coagulation on the removal of natural organic matter (NOM) and disinfection byproduct (DBP) precursors. Twelve natural waters were collected and four treatment scenarios were tested at bench-scale. Results showed that intermediate-ferrate treatment (i.e., coagulation and particle removal followed by ferrate oxidation) was most effective followed by pre-ferrate treatment (i.e., ferrate oxidation followed by coagulation and particle removal (conventional treatment)) or conventional treatment alone (i.e., no oxidation), and the least effective was ferrate oxidation alone (i.e., no coagulation). At typical doses, direct ferrate oxidation of raw water decreased DBP formation potentials (DBPFPs) by about 30% for trihalomethanes (THMs), 40% for trihaloacetic acids (THAAs), 10% for dihaloacetic acids (DHAAs), 30% for dihaloacetonitriles (DHANs), and 5% for haloketones (HKs). The formation potential of chloropicrin (CP) consistently increased after direct ferrate oxidation. Pre-ferrate followed by conventional treatment was similar to conventional treatment alone for NOM and DBP precursor removal. Ferrate pre-oxidation had positive effects on subsequent coagulation/particle removal for THM and THAA precursor removal and may allow the use of lower coagulant doses due to the Fe(III) introduced by ferrate decomposition. On the other hand, intermediate-ferrate resulted in substantially improved removal of NOM and DBP precursors, which can be attributed to initial removal by coagulation and particle removal, leaving precursors that are particularly susceptible to oxidation by ferrate. The Fe(III) resulting from ferrate decay during intermediate-ferrate process was primarily present as particulate iron and could be effectively removed by filtration. Graphical abstract: Highlights: Intermediate-ferrate treatment was most effective for NOM and DBP precursor removal. DBP precursor removal by ferrate followed the order of THAAs > THMs > DHANs > DHAAs > HKs. The benefit of pre-oxidation was diminished when followed by conventional treatment. Ferrate shows similar selectivity for reaction with DBP precursors as ozone.